THE ROLE OF THE TWIN ONION CHIPS SME IN INCREASING RESIDENTS' INCOME IN MABAR HILIR VILLAGE, MEDAN CITY - Syafira Maulida Hasni; Sri Mulyani; Teuku Fahmi (Universitas Dharmawangsa Medan, 2026)
This study examines the role of the Keripik Bawang Nyiur Kembar (Twin Onion Chips) UMKM in increasing the income of residents in Mabar Hilir Village, Medan City. The research problem stems from the limited formal employment opportunities, which limits income for some residents, particularly housewives. The existence of UMKM is an alternative in creating locally-based jobs and helping to increase family income. This study uses a descriptive qualitative research method with an approach focused on understanding the social and economic conditions of the community. Data were obtained through observation, interviews, and documentation with informants consisting of business owners, workers, and local residents. The results show that the Keripik Bawang Nyiur Kembar (Twin Onion Chips) UMKM plays a role in creating employment opportunities for the surrounding community, especially housewives. In addition, this UMKM provides additional income that helps meet family needs and has a social impact in the form of community empowerment and increased local economic activity. However, the UMKM still faces several obstacles such as changing market conditions, limited raw materials, and working conditions. Overall, the Keripik Bawang Nyiur Kembar (Twin Onion Chips) UMKM plays an important role in strengthening the community-based economy